Quality in translation and adaptation for dubbing: Applied research in a professional setting - Spiteri Miggiani, Giselle (The Journal of Specialised Translation, 2023)
Following the proposal of an assessment model that attempts to measure quality in dubbing (Spiteri Miggiani, 2022), this paper presents the data and findings of its application in a professional setting. The study aims to pin down the main translation and adaptation issues affecting quality standards in the professional practice, thereby highlighting them for the sake of translators, trainees, trainers, and other professional roles in the dubbing workflow. The goal is to address these issues through awareness, focused strategies, and dialogue with the stakeholders involved. The model was applied to two translation tasks carried out by a group of established adapters. The tasks were reviewed to identify, categorise, and quantify errors. The data analysis reveals that in one task, the top three errors were related to (1) script functionality, more specifically dubbing notations and character allocation; (2) natural sounding language, more specifically source calques; and (3) translation, more specifically unnecessary loss. In the second task, (1) synchronisation also emerged as a significant challenge, in particular, mismatched labial consonants; together with (2) functionality; and, (3) translation.